Effects of Teacher’ Feedback on Learners: Perspectives of English Majors at a Private University (Journal of Contemporary Educational Policies and Practices, 2023)
Feedback is claimed to be a great contributor to learners’ academic achievements. However, in real-life classrooms, teachers’ feedback-giving practices do not always match learners’ expectations, resulting in adverse effects on learners. This study investigates the frequency, the timing, the manners that the teachers of English majors at Nguyen Tat Thanh University (EFL teachers at NTTU henceforth) delivered feedback on their students’ oral performance, their feedback contents and the influence of their feedback-giving practices on the students’ learning motivation and language achievements. The study adopted a mixed methods research design. The quantitative data were collected from the observation with 10 classes delivered by 10 EFL teachers at NTTU and from the interviews with 30 students attending the 10 classes observed with 3 students per class. The interviews also provided targeted qualitative data. The findings show that not all the teachers recognized the importance of feedback. Some ignored or gave insufficient feedback during teacher-student interactions. In some cases, the teachers’ feedback was too general to help students make any improvements in their performance. Some even provided feedback in a way that negatively influenced the students’ psychology and learning motivation. The findings also reveal the students’ expectations for frequent, timely, constructive feedback given in encouraging manners. The study finally makes some recommendations regarding feedback giving for NTTU teachers.
Keywords: Feedback-giving practices; language achievements; Learning motivation; oral feedback